Determination of Trace Metals and Essential Minerals in Selected Fruit Juices in Minna, Nigeria - A. I. Ajai; S. S. Ochigbo; Z. Abdullahi; P. I. Anigboro (International Journal of Food Science)
Levels of trace metals and essential minerals in selected fruit juice samples purchased from Minna were determined using atomic absorption spectrophotometer (AAS) and Flame photometer. From the obtained result, Cu, Fe, Mn, Na, and Zn were present in all the samples, while Cd, Pb, and Cr were not detectable in all the samples. Concentrations of K range between 1.31 ± 0.10 and 41.20 ± 0.10 mg/100 mL, Na between 15.47 ± 0.15 and 3.50 ± 0.20 mg/100 mL, Mn between Nd and 0.27 ± 0.08 mg/100 mL, Fe between Nd and 0.90 ± 0.05 mg/100 mL, Cu between Nd-0.60 ± 0.00 mg/100 mL, and Zn between Nd-0.09 ± 0.01 mg/100 mL, respectively. The trace metal levels in all the samples were within permissible limit as recommended by WHO for edible foods and drinks and could therefore be taken to compliment the deficiency of these essential minerals from other food sources.